A Rare Case Of Symplastic Leiomyoma Of Uterus : A case Report - Murad Ahmad; Fatima Qaiser Naqvi; Surabhi Gautam; Veena Maheshwari (International Journal of Toxins and Toxics, 2024)
Uterine smooth muscle tumors (USMT) are of mesenchymal origin and develop from the smooth muscle cells of the uterus. Leiomyomas and their subtypes are the most commonly occurring USMT’s. Symplastic Leiomyoma is an unusual histologic subtype of Benign Leiomyoma, hence also known as atypical or Bizarre leiomyoma. It is often difficult to differentiate it from Leiomyosarcoma because of its bizarre looking nuclei on histology. However it’s malignant transformation is rare. Among benign uterine smooth muscle tumors (USMT), symplastic leiomyoma is a unique histologic subtype that is categorized as an unusual or weird leiomyoma. These tumors start in the uterine smooth muscle cells and develop from mesenchymal tissues. Symplastic Leiomyoma is unique among USMTs, leiomyomas, and their subgroups because of its unusual and fascinating histological characteristics. Symplastic leiomyoma and its malignant cousin, leiomyosarcoma, are frequently difficult to distinguish from one another due to the unusual appearance of the tumor's nucleus upon histological inspection. Symplastic Leiomyoma is characterized by strange-looking nuclei, which may cause diagnostic ambiguity because these morphological characteristics may resemble those of malignancies. Because of the nuclei's unusual characteristics, it may be difficult to differentiate them from more severe lesions, which could result in a mistaken diagnosis and cause patients needless anxiety. It is important to stress that, despite the histological similarities, malignant changes in Symplastic Leiomyoma are rare and the tumor usually progresses benignly. Despite the low overall frequency of malignant development in symplastic leiomyoma, proper therapeutic care depends on a precise diagnosis and categorization. In order to ensure that patients with this benign subtype receive the necessary treatment while avoiding needless interventions typically reserved for malignant conditions, pathologists and clinicians can make more informed decisions regarding patient care with the aid of enhanced understanding of the unique histological features and immunohistochemical markers associated with Symplastic Leiomyoma. When it comes to uterine smooth muscle tumors, this thorough understanding is crucial for improving patient outcomes and improving diagnostic strategies.
Keywords: Bizarre Nuclei; Ki-67; Symplastic Leiomyoma; Uterine Leiomyomas